2017
DOI: 10.4315/0362-028x.jfp-17-122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the U.S. Food Safety Modernization Act Produce Safety Rule Standard for Microbial Quality of Agricultural Water for Growing Produce

Abstract: The U.S. Food and Drug Administration (FDA) has defined standards for the microbial quality of agricultural surface water used for irrigation. According to the FDA produce safety rule (PSR), a microbial water quality profile requires analysis of a minimum of 20 samples for Escherichia coli over 2 to 4 years. The geometric mean (GM) level of E. coli should not exceed 126 CFU/100 mL, and the statistical threshold value (STV) should not exceed 410 CFU/100 mL. The water quality profile should be updated by analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 3 publications
11
29
0
Order By: Relevance
“…For example, turbidity was ranked as an important factor in 7 of the 15 random forest analyses performed here, and was associated detecting pathogens in samples collected from both AZ and NY waterways. Multiple studies (Christensen et al, 2000; Francy et al, 2013; Havelaar et al, 2017; Horman et al, 2004; Nagels et al, 2002; Rao et al, 2015; Topalcengiz et al, 2017), including the study reported here and the Ecuadorian study discussed above (Rao et al, 2015), found a positive association between E. coli levels and temperature, or between E. coli levels and turbidity. Francy et al (Francy et al, 2013) surveyed recreational water quality at 22 Ohio beaches along inland lakes and found that turbidity was one of the best predictors of E. coli levels.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…For example, turbidity was ranked as an important factor in 7 of the 15 random forest analyses performed here, and was associated detecting pathogens in samples collected from both AZ and NY waterways. Multiple studies (Christensen et al, 2000; Francy et al, 2013; Havelaar et al, 2017; Horman et al, 2004; Nagels et al, 2002; Rao et al, 2015; Topalcengiz et al, 2017), including the study reported here and the Ecuadorian study discussed above (Rao et al, 2015), found a positive association between E. coli levels and temperature, or between E. coli levels and turbidity. Francy et al (Francy et al, 2013) surveyed recreational water quality at 22 Ohio beaches along inland lakes and found that turbidity was one of the best predictors of E. coli levels.…”
Section: Discussionsupporting
confidence: 45%
“…Similarly, Francy et al (Francy et al, 2013) found that the strength and direction of correlation between water temperature and E. coli levels in 22 Ohio lakes were different for different water sources in the same region. Overall, the findings from this and other studies suggest that turbidity but not temperature may be useful as a supplemental indicator of the microbial quality of surface water (Havelaar et al, 2017; Stocker et al, 2016). Our data do however suggest that temperature is strongly associated with microbial water quality, and inclusion of temperature as a factor in more sophisticated algorithms (e.g., AI tools, machine learning-based predictive risk maps) for predicting when and where water is likely to be contaminated by foodborne pathogens may be useful.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Havelaar et al. () also characterized water sources in Florida in relation to the Subpart E microbial standards and found that E. coli and turbidity were adequate predictors of Salmonella in 150 mL samples for the six water sources sampled. However, the authors note that further mechanistic modeling, including climate and other environmental factors that may affect contamination, is necessary because the statistical criteria in Subpart E by themselves do not allow growers to identify and react to contamination in a timely manner.…”
Section: Key Challengesmentioning
confidence: 99%
“…McEgan, Mootian, Goodridge, Schaffner, and Danyluk (2013) characterized water quality for sources in Florida and found a lack of correlation between Salmonella levels and microbial indicators, as well as a lack of correlation between Salmonella levels and physicochemical indicators. Havelaar et al (2017) also characterized water sources in Florida in relation to the Subpart E microbial standards and found that E. coli and turbidity were adequate predictors of Salmonella in 150 mL samples for the six water sources sampled. However, the authors note that further mechanistic modeling, including climate and other environmental factors that may affect contamination, is necessary because the statistical criteria in Subpart E by themselves do not allow growers to identify and react to contamination in a timely manner.…”
Section: Risk Assessment Is Complicated Due To the Complexity Of Hazamentioning
confidence: 99%